ANALISIS HUKUM TERHADAP PERMOHONAN PAILIT ATAS DEVELOPER DALAM PERJANJIAN PENGIKATAN JUAL BELI APARTEMEN ( STUDI KASUS PUTUSAN MAHKAMAH AGUNG NO. 331 K/PDT. SUS/2012 TANGGAL 12 JUNI 2012) - KARTINI MEILINA H. (PREMISE LAW JURNAL, 2015)
PT Graha Permata Properindo as Developer promised that it will finish the construction work  and physically deliver the apartment in December 2008, but at the time agreed, as Developer, PT. Graha Permata Properindo could not deliver the apartment units to the buyer. The consumers may file the bankruptcy petition against the developer to the Commercial Court because they also act as the creditor for the developer. PT. Bank Tabungan Negara (Persero) Tbk participated in filing an appeal to the Supreme Court against the Decision of Bankruptcy issued by the Commercial Court against the developer because, PT. Bank Tabungan Negara (Persero) Tbk is the creditor for the developer and the developer is still solvent that bankruptcy can inflict loss to the bank as creditor. The legal analysis on the bankruptcy petition against the developer is that elements of credit have been met in the case of bankruptcy petition against the developer. Keywords : Developer, Apartment Trading Agreement, Bankruptcy Petition